An application framework for a situation-aware system support for smart spaces - Santos, Arlindo (2009)
Despite a considerable research eﬀort towards system support for smart spaces, in recent years we have been witnessing a growing perception about a persistent gap between the promises of the area and its real achievements. We are investigating a situation-aware system support for smart spaces that builds on a new set of assumptions and design principles, based on user-controlled associations between global services and local resources. The realisation of this concept raises important challenges across a model for global autonomous applications that enables them to integrate the functionality and resources of multiple situations. This research work aims at investigating such a model and evaluating the concept of situation-aware system support for smart spaces.